2002
DOI: 10.2136/sssaj2002.1143
|View full text |Cite
|
Sign up to set email alerts
|

Models for Estimating Soil Particle‐Size Distributions

Abstract: An accurate mathematical representation of particle‐size distributions (PSDs) is required to estimate soil hydraulic properties or to compare texture measurements from different classification systems. The objective of this study was to evaluate the ability of seven models (i.e., five lognormal models, the Gompertz model, and the Fredlund model) to fit PSD data sets from a wide range of soil textures. Special attention was given to the effect of texture on model performance. Several criteria were used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
2
11

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 29 publications
3
86
2
11
Order By: Relevance
“…According to Fig. 7d, it was found that the fits of PSD models declined with increasing sand content (Hwang et al 2002). On this basis, it can be noted that model performance deteriorated as the sand proportion of soils increased.…”
Section: Sand Groupmentioning
confidence: 75%
See 4 more Smart Citations
“…According to Fig. 7d, it was found that the fits of PSD models declined with increasing sand content (Hwang et al 2002). On this basis, it can be noted that model performance deteriorated as the sand proportion of soils increased.…”
Section: Sand Groupmentioning
confidence: 75%
“…Tested five log-normal models for 71 soils from New Zealand Hwang et al (2002) Evaluated fitting ability at 7 models on 1387 Korean soil samples Hwang (2004) Studied the effect of soil texture of 1387 Korean soil samples on the performance of nine different PSD models Lima and Silva (2007) Conducted a study on PSD of suspended sediments in river water Bah et al (2009) Compared the fitting ability of seven PSD models to data of 55 fine-textured soil samples from New South Wales in Australia Bagarello et al (2009) Evaluated the ability of the hyperbolic and Fredlund models to fit 243 soils Shangguan (2012) Investigated ten PSD models for the conversion of soil texture classification from ISSS and Katschineski to FAO/USDA system for soils from china Botula et al (2013) Evaluated the performance of 18 PSD models for 1412 soils from Central Africa which had humid tropics Weipeng et al (2015) Studied critical evaluation of PSD models of 1013 soil samples from different regions of china Bayat et al (2015) Investigated fitting capability of PSD models on the 713 PSD experimental data of the UNSODA database…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations